Global mercury concentrations in biota: their use as a basis for a global biomonitoring framework - David C. Evers; Joshua T. Ackerman; Staffan Åkerblom; Dominique Bally; Nil Basu; Kevin Bishop; Nathalie Bodin; Hans Fredrik Veiteberg Braaten; Mark E. H. Burton; Paco Bustamante; Celia Chen; John Chételat; et al. (Ecotoxicology, 2024)
An important provision of the Minamata Convention on Mercury is to monitor and evaluate the effectiveness of the adopted measures and its implementation. Here, we describe for the first time currently available biotic mercury (Hg) data on a global scale to improve the understanding of global efforts to reduce the impact of Hg pollution on people and the environment. Data from the peer-reviewed literature were compiled in the Global Biotic Mercury Synthesis (GBMS) database (>550,000 data points). These data provide a foundation for establishing a biomonitoring framework needed to track Hg concentrations in biota globally. We describe Hg exposure in the taxa identified by the Minamata Convention: fish, sea turtles, birds, and marine mammals. Based on the GBMS database, Hg concentrations are presented at relevant geographic scales for continents and oceanic basins. We identify some effective regional templates for monitoring methylmercury (MeHg) availability in the environment, but overall illustrate that there is a general lack of regional biomonitoring initiatives around the world, especially in Africa, Australia, Indo-Pacific, Middle East, and South Atlantic and Pacific Oceans. Temporal trend data for Hg in biota are generally limited. Ecologically sensitive sites (where biota have above average MeHg tissue concentrations) have been identified throughout the world. Efforts to model and quantify ecosystem sensitivity locally, regionally, and globally could help establish effective and efficient biomonitoring programs. We present a framework for a global Hg biomonitoring network that includes a three-step continental and oceanic approach to integrate existing biomonitoring efforts and prioritize filling regional data gaps linked with key Hg sources. We describe a standardized approach that builds on an evidence-based evaluation to assess the Minamata Convention’s progress to reduce the impact of global Hg pollution on people and the environment.

The global challenge of reducing mercury contamination from artisanal and small-scale gold mining (ASGM): evaluating solutions using generic theories of change - Allison R. Aldous; Tim Tear; Luis E. Fernandez (Ecotoxicology, 2024)
Mercury contamination from artisanal and small-scale gold mining (ASGM) currently accounts for 37% of the global total, often affecting tropical regions where regulations, if they exist, are often poorly enforced. Ingestion by people and other animals damages the nervous, reproductive, and cognitive systems. Despite the efforts of many organizations and governments to curb mercury releases from ASGM, it is increasing globally. There are many possible interventions, all with significant complexity and cost. Therefore, we recommend taking an established systematic approach to articulate the current situation and construct theories of change (ToC) for different possible interventions for any government or organization trying to solve this problem. Here we present a high-level situation analysis and generic ToC to support a more coordinated approach that explicitly builds upon previous experience to identify organization- and situation-appropriate engagement on this issue. We then illustrate the use of these generic models to construct a specific ToC with a policy-focused entry point. This includes interventions through (1) engagement with the global Minamata Convention on Mercury; (2) support for existing national laws and policies connected to ASGM and mercury contamination; and (3) engagement of indigenous people and local communities with governments to meet the governments’ legal obligations. By methodically articulating assumptions about interventions, connections among actions, and desired outcomes, it is possible to create a more effective approach that will encourage more coordination and cooperation among governments and other practitioners to maximize their investments and support broad environmental and socio-political outcomes necessary to address this pernicious problem.

A Framework to Integrate Habitat Monitoring and Restoration with Endangered Insect Recovery - Jason Bried; Tim Tear; Rebecca Shirer; Chris Zimmerman; Neil Gifford; Steve Campbell; Kathy O’Brien (Environmental Management, 2014)